1987
DOI: 10.1590/s0074-02761987000800027
|View full text |Cite
|
Sign up to set email alerts
|

Anti-schistosomal drugs: observations on the mechanism of drug resistance to hycanthone, and on the involvement of host antibodies in the mode of action of praziquantel

Abstract: This paper reports recent observations from our laboratory dealing with the anti-schistosome drugs hycanthone (HC) and praziquantel (PZQ). In particular, we discuss a laboratory model of drug resistance to HC in Schistosoma mansoni and show that drug sensitive and resistant lines of the parasite can be differentiated on the basis of restriction fragment length polymorphisms using homologous ribosomal gene probes. In addition, we summarize data demonstrating that effective chemotherapy of S. mansoni infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This lead us to realize that for the majority of research groups, resistance was considered as achieved when at least 90% of the worm population survived a therapeutic dose. In several studies (Dias and Olivier, 1986; Brindley and Sher, 1987; Brindley et al, 1989; Drescher et al, 1993), various lines of schistosomes did not reach this resistance threshold (with or without induction and/or drug pressure over a couple of generations). They were considered as sensitive although in some cases there was a non-negligible percentage (3–26%) of worms surviving a therapeutic dose of either hycanthone or oxamniquine, strengthening our hypothesis that a mechanism following a non-Mendelian inheritance pattern is involved.…”
Section: Discussionmentioning
confidence: 98%
“…This lead us to realize that for the majority of research groups, resistance was considered as achieved when at least 90% of the worm population survived a therapeutic dose. In several studies (Dias and Olivier, 1986; Brindley and Sher, 1987; Brindley et al, 1989; Drescher et al, 1993), various lines of schistosomes did not reach this resistance threshold (with or without induction and/or drug pressure over a couple of generations). They were considered as sensitive although in some cases there was a non-negligible percentage (3–26%) of worms surviving a therapeutic dose of either hycanthone or oxamniquine, strengthening our hypothesis that a mechanism following a non-Mendelian inheritance pattern is involved.…”
Section: Discussionmentioning
confidence: 98%
“…It was observed that in B celldeficient mice the schistosomicide effect of PZQ is strongly reduced or completely abolished. The drug efficacy was completely restored by passive transfer of immune serum obtained from S. mansoni infected donor mice at the acute phase [78]. In immunologically intact mice, the efficacy of PZQ can be enhanced by the passive transfer of sera from rabbits immunized with S. mansoni adult worm antigens [79], or by vaccination with a preparation of worm membrane antigens [80].…”
Section: Pzq Mechanism Of Actionmentioning
confidence: 99%
“…Combining artemether with praziquantel appears to produce a synergistic killing of adult worms [28] . The prospects seem good for prophylaxis with artemether in high-risk groups in areas where schistosomiasis is endemic, such as flood relief workers, tourists and fishermen [29] . The doses required are lower than those required for treatment of malaria, but it is unlikely that artemether would be used in areas where malaria is endemic, because such use might lead to the selection of artemether-resistant Plasmodium falciparum .…”
Section: Treatment Medicalmentioning
confidence: 99%